(untitled) (Research, Society and Development, 2021)
The Unified Health System enables the promotion of universality, so in 2011 the National Policy for Integral Health of Lesbians, Gays, Bisexuals, Transvestites and Transsexuals was instituted. Lesbian and bisexual women face numerous obstacles in the search for access to health services, which may be related to the invisibility of female sexuality, to prejudice due to their sexual orientation. It is noted that the nursing professional is the one that is closest to the population in health services, especially in Primary Care. The study aimed to identify health care for lesbian and bisexual women performed in primary care. This is an Integrative Review (IR) being developed following the six steps proposed by Mendes, Silveira and Galvão (2019). The search and selection of articles was carried out in August and September 2020, in the databases and portals: MEDLINE, IBECS, BDENF, via the Virtual Health Library (VHL), LILACS and SCIELO portal through capes portal. Using the descriptors "Female Homosexuality", "Bisexuality" and "Integrality in Health", through the Boolean operator "AND". Lesbian and bisexual women are not fully welcomed and assisted according to their health needs. The lack of information, prejudice or lack of interest in relation to the inclusion and specificities of these women is evaluated as worrying. It is perceived that there is no welcoming environment for there to be comfort in expressing your sexuality, as well as, to answer their doubts.